Immunosuppression and the Immune Response to Transplantation - David Ludwin; Dianne Arlen; J David Russell (Canadian Journal of Infectious Diseases)
OBJECTIVES: To review the roles of allorecognition, transplant rejection, and immunosuppressive therapy in predisposing patients to viral infections. DATA SOURCES: Computer and bibliography searches were used to identify relevant articles. STUDY SELECTION AND DATA EXTRACTION: Both review and single articles were critically assessed with respect to data analysis and clinical relevance. CONCLUSIONS: Advances in our knowledge about the nature and regulation of the immune response has enhanced our understanding of the etiology of transplant rejection. Host factors and immunosuppressive therapy may both be important in modulating the immune response after transplantation. Viral infections in the post-transplant period occur not only as a consequence of the immunocompromised state. but viruses themselves may either augment immunosuppression or initiate rejection.